Investigating the Occurrence of Soil-Transmitted Parasites Contaminating Soil, Vegetables, and Green Fodder in the East of Nile Delta, Egypt - Samah H. Yahia; Samia E. Etewa; Abd Allah A. Al Hoot; Salwa Z. Arafa; Nesreen S. Saleh; Mohamed H. Sarhan; Suzan I. Rashad; Shimaa S. Hassan (Journal of Parasitology Research)
Background. Food-borne parasites are major sources of human and animal illness, posing severe health risks in places with contaminated soil, poor water quality, cleanliness, and poor sanitation. The usage of untreated organic fertilizers arising from the excreta of the parasites’ definitive hosts either man or animal pollutes the agricultural soil and is reflected in its products of vegetables and green fodders causing serious health problems. Therefore, to the best of our knowledge, this will be the first study that investigated the combination of parasitic contamination of the agricultural soil and its products of raw eaten vegetables and green fodder in East Nile Delta, Egypt. Aim. The purpose of this study was to investigate the type and degree of contamination caused by parasites in regularly used raw vegetables, green fodder, and soil samples collected from open fields in Egypt’s East Nile Delta. Study Procedures. A cross-sectional study comprised a simple random collection of 400 soil samples, 180 green fodder samples, and as well as 400 vegetable samples, including lettuce, radish, coriander, parsley, dill, watercress, tomatoes, green pepper, cucumber, and carrot, that were gathered throughout one year period from January to December 2021 to represent all seasons (winter, spring, summer, and autumn). The research locations were chosen from various open green fields and farming regions in Egypt’s East Nile Delta producing ready-to-eat vegetables for human consumptions and planting green fodder for animal feeding. Concentrations, including sedimentation, and flotation, and staining techniques were used to recover the greatest number of parasitic life forms. The parasitic structures discovered were identified using biometric and imaging data and compared with known parasite morphology. Statistical analysis was performed with the SPSS software version 22 (IBM, Chicago, IL, USA). Data were presented in numbers and percentages. P-values equal to or less than 0.05 were considered to be statistically significant. The difference in parasitic contamination among the different categories was compared using the chi-square test. Results. In this investigation, 243 out of 400 soil samples (60.7%) confirmed positive for parasitic contamination (P<0.05). Various parasitic life forms were significantly found in 249 out of 400 (62.25%) of the vegetable samples, with (65.1%) of them harboring one parasite species, whereas 9.2% significantly contained up to three parasites. Ascaris eggs, Trichuris eggs, and Giardia cysts were the most prevalent parasites, which were predominantly isolated from vegetables with uneven surfaces. 109 of 180 (60.0%) green fodder samples confirmed insignificantly positive for parasitic pollution. The proportion of parasite contamination in vegetable samples was insignificant although the highest was in spring (29.3%), followed by summer (27.7%), whereas it is significant in autumn (24.5%). The prevalence rate was the lowest in winter (20.1%). Conclusion and Recommendations. Our findings demonstrated a significant load of parasites notably the soil-transmitted parasitic infection in raw vegetables and green fodder cultivated in open fields as well as in their mother soil in the east of the Nile Delta, Egypt. These results confirm the urgent need to deploy strict control measures to the soil, especially during the pre-harvest period of raw eaten vegetables and green fodder, a critical step in reducing food-borne transmission of soil-transmitted parasites to man and animals.